Local piezoresponse and polarization switching in nucleobase thymine microcrystals - Bdikin, Igor (2017)
Thymine (2-oxy-4-oxy-5 methyl pyrimidine) is one of the four nucleobases of deoxyribonucleic acid (DNA). In the DNA molecule, thymine binds to adenine via two hydrogen bonds, thus stabilizing the nucleic acid structure and is involved in pairing and replication. Here, we show that synthetic thymine microcrystals grown from the solution exhibit local piezoelectricity and apparent ferroelectricity, as evidenced by nanoscale electromechanical measurements via Piezoresponse Force Microscopy. Our experimental results demonstrate significant electromechanical activity and polarization switchability of thymine, thus opening a pathway for piezoelectric and ferroelectric-based applications of thymine and, perhaps, of other DNA nucleobase materials. The results are supported by molecular modeling of polarization switching under an external electric field. (C) 2015 AIP Publishing LLC.